ANALISIS IMPLEMENTASI KEBIJAKAN RELOKASI PEDAGANG KAKI LIMA (PKL) KAPAL MENDOAN (MANGAN ENAK KARO DOLAN) KABUPATEN KEBUMEN MENGGUNAKAN PRINSIP GOOD GOVERNANCE - Aditya Winarman; Satria Aji Imawan (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
The Government of Kebumen Regency established a policy to relocate street vendors (PKL) from the Alun-alun of Kebumen Regency to Kapal Mendoan through Kebumen Regent Regulation Number 51 of 2024 concerning the Location and Schedule of Street Vendors’ Business Activities. In its implementation, the relocation policy is considered not to have been implemented optimally, as several problems were identified, resulting in Kapal Mendoan having limited attractiveness and a significant number of vacant kiosks. This study aims to analyze the implementation of Good Governance principles as well as the supporting and inhibiting factors of the street vendor relocation policy at the Alun-alun of Kebumen Regency, with Kapal Mendoan as the case study. This research employs a qualitative research method, with data collected through interviews, observations, and literature review. The results indicate that the relocation policy of street vendors at the Alun-alun of Kebumen Regency has been less effective, as there are still obstacles in the dimensions of transparency, accountability, rule of law, and effectiveness and efficiency, although the dimensions of participation and equity have been implemented relatively well. The supporting factor in the implementation of the relocation policy is communication, while the inhibiting factors include resources, bureaucratic structure, and disposition.